Kesuburan Perairan dan Komunitas Fitoplankton Danau Toba di Wilayah Kecamatan Ajibata Kabupaten Toba Samosir - Yudhi Soetrisno Garno (BRIN Publishing (Penerbit BRIN), 2022)
In order to determine the waters fertility and Phytoplankton abundance of Lake Toba in the Ajibata District, and to compare them with other sub-districts in Lake Toba, this study was conducted. The research was conducted by in-situ observation and sampling for laboratory analysis according to ISO 5667-6:2014 and ISO 5667-3:2012 procedures. This study revealed that the waters of Lake Toba in the District of Ajibata contain total dissolved inorganic nitrogen (nitrite-N, nitrate-N and NH4-N) dissolved 0.158–0.290 mg/l; and total phosphate 0.040–0.060 mg/l. This indicates that the waters are already included in fertile waters. These waters are inhabited by at least 24 types of phytoplankton which are included in 4 classes, namely Bacillariophyceae (11 sp.), Chlorophyceae (8 sp.), Cyanophyceae (3 sp.) and Dinophyceae (2 sp.). Even though they are fertile waters, when compared to the waters of Lake Toba in other sub-districts, the concentration of inorganic nitrogen and total phosphate is still much lower. This study also revealed that the presence of floating net cage (KJA) greatly affected the concentration of dissolved nitrogen and phosphate as well as the abundance of phytoplankton in the vicinity. This study did not show a positive correlation between nutrient concentration and abundance of phytoplankton where waters with higher nutrient concentrations did not always have a higher abundance of phytoplankton.